«Con assoluta sincerità» Il lavoro editoriale di Natalia Ginzburg (1943-1952) - Bassi, Giulia (Studi di letterature moderne e comparate, 2023)
«With absolute honesty»: this is how Natalia Ginzburg worked in her editorial job at the Einaudi publishing house. Through documents from the Einaudi Archives in Turin and the Archivio del Novecento (Sapienza University), this book traces Ginzburg's editorial work in the postwar period, when she had major editorial responsibility and coordinated the translation of Proust's Recherche. The correspondences with authors and translators restore a new profile of the writer, bringing to light the relevance of her intervention in narrative series, such as "Coralli" and "Gettoni"; the interaction between the professions of writer, editor and translator, from which recurring elements of poetics emerge; and the issues involved in being the only woman to have a decision-making role in the Einaudi editorial staff of the time.